Editors note - Nordkvelle, Yngve (Seminar.net, 2017)
Lifelong learning is a recurring theme in this journal. The present issue of Seminar.net has four contributions, covering a range from how elderly use ICT, how teachers and supervisors in higher education experience virtual learning environments, how producers of MOOC’s fail to observe quality frameworks, and last how “gamification” affects ideas about teaching and learning. They all bring vital arguments to the table about how digital environments cause changes in our lives, beginning with games for children and helping elderly to adjust to an increasingly digitized lifeworld in the other end of the life cycle. First, most of the technological innovations we are used to by now, was invented a long time ago – by persons who now are considered elderly. The ideologies supported around notions like “the digital natives” are exactly that, - ideologies. But even skilled and experienced elderly – and teachers in higher education are in dire need of keeping up with swift changes in technology and its use. I am very pleased that the articles we present here have a critical stance towards ideologies and are able to scrutinise the conditions for a democratic and factual base for education. The opening article in this issue, “Older active users of ICTs make sense of their engagement”by Magdalena Kania-Lundholm and Sandra Torres, who work at Uppsala University, Sweden enlightens us about how elderly people use digital media. Instead of seeing the elderly as a group of “digital immigrants”, this article focuses on elderly people who are active and skilled users of ICT. They are eager to share their skills and experiences and contribute to the wellbeing of other, not so eager users. The article contributes to the notion of “the digital spectrum” and furthers the very important discussion on the inequalities that using ICT continues to bring about. The second article is written by Chris O’Toole, of Lancaster University, and has the title “Networked e-Learning: The changing facilitator - learner relationship, a facilitators’ perspective; A Phenomenological Investigation”. The phenomenological case study deals with how the relationship between facilitator and student is changing. Networked e-Learning is the context and the research is undertaken at an Irish higher education institution.The author’s role as a highly experienced facilitator provides particular and specific insight into the guiding facilitator’s experiences during a time of institutional transition to Networked e-Learning. Gamification is a topic that has been declared as “up and coming” for a number of years. Marc Fabian Buck, of the Nord University, Norway, presents the article “Gamification of learning and teaching in schools – a critical stance”. He states that the aim of Gamification is to change learning for the better by making use of the motivating effects of (digital) games and elements typical of games, like experience points, levelling, quests, rankings etc. His most contemporary example is of the “Summer of ‘16” and the apparent success of “Pokemon go”. He argues that gamified learning and teaching suspends the fundamental, subversive, and critical moments only schools can offer. The last article is provided by Ulf Olsson, of Stockholm University, Sweden: “Teachers’ Awareness of Guidelines for Quality Assurance when developing MOOCs”. His study focuses on higher education teachers’ awareness of quality issues in relation to Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG). Olsson conducted semi-structured interviews with 20 teachers at six Swedish HEIs while they developed open courses (MOOCs). The overall findings show that the teachers were not part of any transparent quality assurance system. Subsequently, he raises the question of the adequacy of a quality system for innovative activities.